Methyltrioxorhenium (MTO) catalysis in the epoxidation of alkenes: a synthetic overview. (13th January 2022) - Verma, Saumya; Joshi, Asha; De, Saroj Ranjan; Jat, Jawahar L.
Abstract : Epoxides are biologically important moiety that is also used as synthetic intermediates. This review aims to present the up-to-date advancements in methyltrioxorhenium (MTO)-catalyzed epoxidation of alkenes using diverse oxidizing agents. Abstract : Epoxidation of alkenes is one of the most explored reactions in organic synthesis because of the accessibilities of diverse important compounds from epoxides. Several transition-metal catalysts, in combination with oxidizing agents, have been successfully utilized to achieve alkene epoxides. In this context, methyltrioxorhenium (MTO)-catalyzed epoxidation of alkenes in accordance with different oxidants has been widely reconnoitred where the Lewis acidity of rhenium (Re) is diminished by different Lewis bases to suppress the decomposition of epoxides to diols. Although great success has been accomplished, no review article on MTO-catalyzed epoxidation has been published to date. Therefore, all the advancements in methyltrioxorhenium (MTO)-catalyzed epoxidation of alkenes using different oxidizing agents (aq. H2 O2, urea-H2 O2, and sodium percarbonate) have been summarized in this comprehensive review article for the scientific community.